2x+3(4-5+5)=6-6+7

Simple and best practice solution for 2x+3(4-5+5)=6-6+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3(4-5+5)=6-6+7 equation:


2x+3(4-5+5)=6-6+7

We simplify the equation to the form, which is simple to understand
2x+3(4-5+5)=6-6+7

Simplifying terms in parentheses
2x+3*(+4)=6-6+7

Reorder the terms in parentheses
2x+(+12)=6-6+7

Remove unnecessary parentheses
+2x+12=+6-6+7

We move all terms containing x to the left and all other terms to the right.
+2x=+6-6+7-12

We simplify left and right side of the equation.
+2x=-5

We divide both sides of the equation by 2 to get x.
x=-2.5

See similar equations:

| ln(9x+10)-ln(x)=ln(10) | | 14-(9t-2)=-t+30 | | -3(-c-18)=-3-18 | | (5x+10)+58=(11x+2) | | 9x^2-25x+16=0 | | 8x^2-28X+24=0 | | .5t-3t+5=0 | | 52+x=2(27+x) | | 0.8b-3.4b+15.61=-13.39-2.6b | | 48=8x+2 | | 6x+7x-36=90-5x | | 4(x+2)=2(2x+5)-2 | | 9.22-2.2t=-2.2t+9.22 | | 5(7-2x)=-55 | | (3i)(-5i)= | | 40-4=2w | | X^2+8x+3=7 | | 3.5y+5-1.5y=8 | | -(6x+2)=-4(-7-6x) | | 2x+8+5=180 | | 20k+19=18k+19+2k | | y-3-4y=12 | | 29=5 | | -2x+4+6x=5x-3a | | 121=11a | | 3-13=11-5y | | 9(t-4)+3t=6(2t+4)-11 | | 5x+(x+1)4=h | | 9(t-4)+3t=2t+4-11 | | 4x+43+12=180 | | x-9x=4x-9-x | | -x=a-2x |

Equations solver categories